Effect of deformation by equal-channel multiangle pressing on functional properties of NbTi-based superconductor - Beloshenko, V.A.; Dyakonov, V.P.; Chishko, V.V.; Matrosov, N.I.; Mironova, O.N.; Gajda, D.; Zaleski, A.J.; Puzniak, R. (Functional Materials, 2009)
Influence of predeformation by the equal-channel multiangle pressing combined with hydroextrusion, drawing and heat treatment on structure and physico-mechanical properties of superconducting Nb + 60 at. % Ti alloy wire has been investigated. Effect of deformation on pinning force in the alloy has been estimated. Досліджено вплив величини попередньої деформації методом рівноканального багатокутового пресування у сполученні з гідроекструзією, волочінням і термообробкою на структуру й фізико-механічні властивості надпровідного дроту на основі сплаву Nb + 60 ат. % Ті. Зроблено оцінку впливу деформації на силу пінінгу у сплаві. Исследовано влияние величины предварительной деформации методом равноканального многоуглового прессования в сочетании с гидроэкструзией, волочением и термообработкой на структуру и физико-механические свойства сверхпроводящей проволоки на основе сплава Nb + 60 ат. % Ti. Произведена оценка влияния деформации на силу пиннинга в сплаве.